Clinical, mechanical and histological evaluation of antifreeze peptide type 1M cryopreserved skin in tissue transplantation - Ibrahim, Sahar Mohammed (2017)
Cryopreservation of tissues and cells has witnessed a magnificent attention in the scientific society since 1949, when Polge had discovered the cryoprotective properties of glycerol to preserve sperm. Later with the progress of using of autogenic and allogeneic tissues, the need for developing new compounds and techniques for the cryopreservation of living tissues is increasing but the freezing damage represent one of the biggest challenging issues facing the maintenance of functional and structural integrity of living tissues after cryopreservation. All approaches for cryopreservation aim to overcome the biological, chemical, mechanical and thermal stresses of ice crystal formation and re-crystallization associated with subzero cryopreservation. The objectives of our study is to establish a cryopreservation technique to preserve living tissues by using antifreeze peptide type 1m (Afp1m) and to evaluate its ex vivo in vivo and in vitro effects on the mechanical, clinical, and histological properties of skin grafts by using different microscopic imaging techniques. This study was able to determine the effects of freezing on skin samples, skin fibroblasts (M.dunni clone (1118C), and skin grafts cryopreserved with Afp1m in different concentrations (3 and 5 mg/ml; at -4 and/or -8 ᵒC for up to 72 hrs). Histological and immunohistological examination of ex vivo skin samples showed that skin graft cryopreserved in 5mg/ml at 24, 48 and 72 hrs. have the best expression of TGF and VEGF and also have the best preserved morphological appearance as compared to 3mg/ml and control (80% glycerolized tissue) at -4 and -8 ᵒC. Cell viability studies showed that the viability of skin fibroblasts cryopreserved in 5mg/ml at 24, 48 and 72 hrs. was better as compared to 3mg and control at -4 and -8ᵒC. Cell toxicity assessment indicates that Afp1m do not have toxic effects on skin fibroblasts growth. While the level of DNA damage in skin fibroblast cryopreserved with AFP was higher at -8 ᵒC especially at lower concentration as compared to -4 ᵒC .There was significant difference (P ˂0.05) between DNA damage at two temperatures, the level of DNA damage in cell cryopreserved with 3 mg/ml of AFP was higher than those cryopreserved with 5 mg/ml of AFP at -8 ᵒC. The in vivo study was performed on 24 rats with 208 ± 31 g body weight (mean ± SD), and age eight- weeks old. Rats (n=24) were divided into four groups. One-two circular full-thickness 1.5-2.5 cm diameter wounds were created on the backs of rats. Non-cryopreserved and cryopreserved auto skin grafting were placed onto the wound area and stitched. Grafts were bandages. Wounds were monitored macroscopically and evaluated clinically at days 5, 8, 11, 14, 17, 20 and 22 post-operation. All skin grafts were subjected to histological and mechanical examinations at the end of experiment, while blood samples were collected from all rats at week one and at end of experiment for toxicity analysis. The clinical results showed a significant difference (P ˂0.05) among 4 groups in pliability of skin grafts ,adherence to the underling bed, and in the color of skin grafts (P <0.05), (P <0.05), and (P <0.05) respectively. The results of mechanical properties showed no significant difference (P ˃0.05) among the 4 experimental groups in maximum load, tensile stress at maximum load, tensile strain at maximum load, and elasticity (P >0.05), (P >0.05), (P >0.05), and (P >0.05) respectively .However the results of non transplanted skin strips cryopreserved in glycerol, Afp1m showed significant difference (P ˂0.05) in maximum load only. The histological results showed a significant difference among 4 groups in epidermal integrity, dermal-epidermal junction (P <0.05) and (P <0.05) respectively. The results of liver enzymes ALT & AST and total bilirubin showed no significant difference between weeks 1 and 3 (P > 0.05), (P >0.05), and (P >0.05) respectively and among the 4 experimental groups as compared to normal values ( P >0.05), (P >0.05), and (P >0.05) respectively. In conclusion, Afp1m was found beneficial that could serve as an efficient agent for skin grafts cryopreservation.